The dental esthetic screening index: A new tool for assessment of dento-facial esthetics in restorative dentistry - Frese, Cornelia; Leciejewski, Florian; Specht, Regina; Wohlrab, Theresa Friederike; Büsch, Christopher; Bömicke, Wolfgang; Probst, Kirsten; Katsikogianni, Eleni; Wolff, Diana (Journal of esthetic and restorative dentistry, 2019)
Objectives There is a lack of comprehensive indexes, which can measure conditions or changes in dento-facial esthetics before and after treatment. Therefore, the 12-item Dental Esthetic Screening Index (DESI) was developed and validated. Materials and Methods Reliability was tested by five dental professionals, who evaluated 30 standardized patient photographs baseline and after 14 days. Clinical validation was done on 52 patients before and after restorative treatment. For subjective assessment, patients completed a validated questionnaire before and after treatment. Statistical analysis included inter and intrarater reliability, Wilcoxon test and linear regression analysis. Results The single item analysis identified two weak extraoral items (κ = 0.15; κ = −0.05), that were removed from the DESI. After this modification, both inter- (κ = 0.83-0.86) and intrarater reliability (ICC1-5 = 0.75-0.86) were in excellent to good agreement. In the clinical validation, the DESI was significantly lower after restorative treatment (P < .0001). The patients' perception questionnaires showed significant improvement after restorative therapy (P < .0001). A correlation of the DESI and the results of patients' perception questionnaires could be assumed (P < .0001; R2 = 0.32). Conclusions The DESI was found to be a reliable and valid instrument for the quantitative assessment of dento-facial esthetics. It correlated well with the subjective assessment of the patients. Clinical Significance This comprehensive index would allow for objective quantification of clinical situations, for reliable baseline and outcome assessment in esthetic dentistry. As patients' esthetic feelings and sensations are subjective, this objective index is also proven to be congruent to patients' individual subjective assessment of dento-facial esthetics.
Gesehen am 23.04.2020